2003
DOI: 10.1051/0004-6361:20030387
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric flows measured with TRACE II. Network formation

Abstract: Abstract. We analyse a 7 d (167 h) sequence of TRACE white-light images with 1 angular resolution taken at 1 min cadence. The TRACE resolution and the fast cadence allows us to produce maps of the horizontal flow fields with high angular (1 ) and temporal resolution (5 min). The field of view of 128 × 128 (≈93 Mm × 93 Mm) covers approximately an area of 10 to 30 supergranules. This area was followed during solar rotation. Magnetic flux was artificially inserted into the successive flow maps in the form of ephe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In the future it would be very useful to perform simulations such as the ones performed by Simon et al (2001) and Krijger & Roudier (2003) by including solar cycle variations of parameters such as the supergranulation size (see Sect. 4.2) in order to help to interpret these new results.…”
Section: Resultsmentioning
confidence: 99%
“…In the future it would be very useful to perform simulations such as the ones performed by Simon et al (2001) and Krijger & Roudier (2003) by including solar cycle variations of parameters such as the supergranulation size (see Sect. 4.2) in order to help to interpret these new results.…”
Section: Resultsmentioning
confidence: 99%
“…As far as the horizontal velocities are concerned, the tracking of magnetic network elements gives values around 350 m s -1 , close to the estimates derived from granule tracking (Lisle et al, 2000). Krijger and Roudier (2003) found that the chromospheric network is well reproduced by letting magnetic elements that are emerging be passively advected by the surface (supergranulation) flow field. These results suggest that the formation of the magnetic network is in some way related to the supergranulation flow.…”
Section: Supergranulation and The Magnetic Networkmentioning
confidence: 98%
“…Rieutord et al 2000;Krijger & Roudier 2003). The quality of the data (free of atmospheric seeing) and the length of the time sequence allow us to provide a very clear illustration of this phenomenon.…”
Section: Corks and Magnetic Fieldsmentioning
confidence: 99%